High Exogenous Antioxidant, Restorative Treatment (Heart) for Prevention of the Six Stages of Heart Failure: The Heart Diet - Ram B. Singh; Jan Fedacko; Dominik Pella; Ghizal Fatima; Galal Elkilany; Mahmood Moshiri; Krasimira Hristova; Patrik Jakabcin; Natalia Vaňova (MDPI AG, 2022)
The exact pathophysiology of heart failure (HF) is not yet known. Western diet, characterized by highly sweetened foods, as well as being rich in fat, fried foods, red meat and processed meat, eggs, and sweet beverages, may cause inflammation, leading to oxidative dysfunction in the cardiac ultra-structure. Oxidative function of the myocardium and how oxidative dysfunction causes physio-pathological remodeling, leading to HF, is not well known. Antioxidants, such as polyphenolics and flavonoids, omega-3 fatty acids, and other micronutrients that are rich in Indo-Mediterranean-type diets, could be protective in sustaining the oxidative functions of the heart. The cardiomyocytes use glucose and fatty acids for the physiological functions depending upon the metabolic requirements of the heart. Apart from toxicity due to glucose, lipotoxicity also adversely affects the cardiomyocytes, which worsen in the presence of deficiency of endogenous antioxidants and deficiency of exogenous antioxidant nutrients in the diet. The high-sugar-and-high-fat-induced production of ceramide, advanced glycation end products (AGE) and triamino-methyl-N-oxide (TMAO) can predispose individuals to oxidative dysfunction and Ca-overloading. The alteration in the biology may start with normal cardiac cell remodeling to biological remodeling due to inflammation. An increase in the fat content of a diet in combination with inducible nitric oxide synthase (NOSi) via N-arginine methyl ester has been found to preserve the ejection fraction in HF. It is proposed that a greater intake of high exogenous antioxidant restorative treatment (HEART) diet, polyphenolics and flavonoids, as well as cessation of red meat intake and egg, can cause improvement in the oxidative function of the heart, by inhibiting oxidative damage to lipids, proteins and DNA in the cell, resulting in beneficial effects in the early stage of the Six Stages of HF. There is an unmet need to conduct cohort studies and randomized, controlled studies to demonstrate the role of the HEART diet in the treatment of HF.